HADIS PERSPEKTIF SAHRUR; Studi Penafsiran Terhadap Hadis Nabi SAW - ROBBY ZIDNI ILMAN ZF (Ma'had Aly PP. Zainul Hasan Genggong, 2023)
“Standardization” of hadith’ interpretation is a religious understanding manifest Top of Form “Establishment” in hadith interpretation is a manifesto carries religious understanding entity; not only in the form of interpretation entity, understanding entity, truth entity, Islam entity, but also the other entity in religion. This artical discass one ofcontemporary muslim scholar.Muhammad Sahrur, Who has concern on al-Qur’an, and expalain a bout sunnah al-rasuliyah and sunnah al-nabawiyah. According to Muhahmmad Sahrur, he said sunnah is a method of appllicate the laws that listed on ummul kitabeasly without out limitations in case of problems that related with limit (Hudud). We can understand that sunnah is the method called Hermeneutic. These clasification of sunnah help to understanding the content of sunnah. Such as discussion in hudud and pray of sholat. Muhammad Sahrur think all of matan not sanad only. They examine not only the horizon of the text (matan), the originator of the horizon (the Prophet), the reader (rijal al-hadith, mukharrij al-hadith, also mufassir), but also its contextuality. Nevertheless, for “established” hadith diciplines, hermeneutic is a “supporting instrument” (not replacing instrument), however, it is perceived able to create interpretation by combining textuality element and hadith contextuality through this hermeneutic approach at once, since a text could only come together in a context.